Phylogenetic diversity of nonmarine picocyanobacteria. Issue 2 (15th April 2013) - Callieri, Cristiana; Coci, Manuela; Corno, Gianluca; Macek, Miroslav; Modenutti, Beatriz; Balseiro, Esteban; Bertoni, Roberto
Abstract: We studied the phylogenetic diversity of nonmarine picocyanobacteria broadening the sequence data set with 43 new sequences of the 16S rRNA gene. The sequences were derived from monoclonal strains isolated from four volcanic high‐altitude athalassohaline lakes in Mexico, five glacial ultraoligotrophic North Patagonian lakes and six Italian lakes of glacial, volcanic and morenic origin. The new sequences fall into a number of both novel and previously described clades within the phylogenetic tree of 16S rRNA gene. The new cluster of Lake Nahuel Huapi (North Patagonia) forms a sister clade to the subalpine cluster II and the marine Synechococcus subcluster 5.2. Our finding of the novel clade of 'halotolerants' close to the marine subcluster 5.3 ( Synechococcus RCC307) constitutes an important demonstration that euryhaline and marine strains affiliate closely. The intriguing results obtained shed new light on the importance of the nonmarine halotolerants in the phylogenesis of picocyanobacteria.